2021
DOI: 10.1186/s13028-021-00592-0
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid treatment for acute/acute-on-chronic experimental and naturally occurring pancreatitis in several species: a scoping review to inform possible use in dogs

Abstract: Acute pancreatitis in dogs is a prevalent disease characterised by mild to severe inflammation. Treatment with anti-inflammatory corticosteroids has been widely debated but is not generally recommended in veterinary medicine. The objective of the present study was to present current evidence on the effect of corticosteroid treatment for acute/acute-on-chronic pancreatitis across species. These findings were then used to evaluate if and how corticosteroid treatment could influence disease outcome in canine acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
(326 reference statements)
0
6
0
Order By: Relevance
“…75 A recent review, evaluating data from multiple species, suggested that corticosteroids might have a positive effect on outcome in the treatment of acute or acute on chronic pancreatitis in dogs. 76 Several early studies documented a potential relationship between organophosphates and the development of AP. Sublethal doses of organophosphate anticholinesterase ex vivo results in AP in dogs as determined by histopathology.…”
Section: Drugs/toxinsmentioning
confidence: 99%
“…75 A recent review, evaluating data from multiple species, suggested that corticosteroids might have a positive effect on outcome in the treatment of acute or acute on chronic pancreatitis in dogs. 76 Several early studies documented a potential relationship between organophosphates and the development of AP. Sublethal doses of organophosphate anticholinesterase ex vivo results in AP in dogs as determined by histopathology.…”
Section: Drugs/toxinsmentioning
confidence: 99%
“…4,10,41,43 Immune-mediated CP is reported in cocker spaniel and Cavalier King Charles spaniel breeds in the United Kingdom 5,44 and administrating glucocorticoids or cyclosporine is reported in dogs and cats with CP and AP to suppress inflammation. 45,46 Immunosuppressive therapy was not associated with the clinical score or with serum DGGR-lipase activity changes (either improved or worsened) herein;…”
Section: Discussionmentioning
confidence: 79%
“…Immune‐mediated CP is reported in cocker spaniel and Cavalier King Charles spaniel breeds in the United Kingdom 5,44 and administrating glucocorticoids or cyclosporine is reported in dogs and cats with CP and AP to suppress inflammation 45,46 . Immunosuppressive therapy was not associated with the clinical score or with serum DGGR‐lipase activity changes (either improved or worsened) herein; nevertheless, these results should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 92%
“…Administration of corticosteroids to healthy dogs does not result in significant changes in cPLI concentrations or does not commonly (1/6) increase serum cPLI concentrations into a diagnostic range for pancreatitis [ 38 , 39 ]. Indeed, corticosteroids are now being used with increasing frequency in the management of acute pancreatitis [ 40 , 41 ]. In contrast with those results, our study showed a moderate frequency of corticosteroid use prior to sampling in dogs with increased Spec cPL concentrations, and this may reflect the presence of concurrent disease treated with corticosteroids or secondary pancreatic inflammation influenced by concurrent disease [ 8 ].…”
Section: Discussionmentioning
confidence: 99%